IMPROVING DESCRIPTIVE WRITING SKILL TROUGH MIND MAPPING TECHNIQUE OF GRADE SEVEN STUDENTS AT MTS TAHFIZH AL MADINAH MALANG - Binti Masruroh (Language-Edu, 2021)
Abstract            The purpose of this research is to improve the students’ writing ability in descriptive text using mind mapping technique. The research was conducted for 7th grade students of MTS Tahfizh Al Madinah Malang because the researcher found that the ability of these students were lower than the passing grade set. This condition was caused by the passiveness of the students in using English both in asking or answering questions. Therefore, the researcher was intended in taking a classroom action research by applying an appropriate technique to help these students. And mind mapping technique was chosen to be applied here.            To do the research, the researcher applied Collaborative Classroom Action Research design where the collaboration between researcher and teacher is applied to plan, implement, observe, and evaluate the actions taken.The two cycles are applied here; and each cycle contains four primary stages, i.e. action planning, implementation, classroom observation, and reflection. The main data used in this research is taken from the writing test result. And the secondary data was obtained from the interview and documentation.            The students’ average writing score for the first cycle was M=71, while the targeted average score was M>75. The number of students who reached the score target was only 63%, below the targeted percentage number, 85%. Then, the action taken proceeded the second cycle was using pictures and write down keywords for those. Then, the students’ average writing score improved; it was M=77. The number of the students who reached the targeted score improved as well, 88%.  It means that there was improvement in students’ writing skill in the second cycle.            So, it can be concluded that the using of mind mapping technique could help 7th students of Mts. Tahfizh Al Madinah Malang to improve their skill in writing descriptive text.  Keywords: Writing ability, Descriptive Text, Mind Mapping